The demographic characteristics of patients seeking health care for infant and childhood illnesses at Nepal Medical College and Teaching Hospital - Pandey, Kishore Raj; Kafle, Phanindra Prasad; Karki, Debendra (Occasional Papers in Sociology and Anthropology, 2008)
DOI: 10.3126/opsa.v8i0.1129 Occasional Papers in Sociology and Anthropology Vol.8 2003 p.218-226